English Corner Using Creative Work: Supplement and Booster to Enhance Students’ English Performance - Etika - Rachmawati; Rina - Herlina (JALL (Journal of Applied Linguistics and Literacy), 2023)
This study aims to investigate EFL students’ perception of English Corner (EC) and how EC is constructively designed and developed in English Education at Galuh University as a non-credit course that consists of five programs that all participants might optionally select dealing with their interests and talent. Singing, poetry reading, storytelling, drama, and public speaking are sophisticated complete packages to predominantly uphold participants’ English performance due to English as the only language used in EC. It is as opposed to the preliminary EC that originated in China that was undertaken for the public elsewhere. However, EC at Galuh University consists of the statement of the problem of this study consists of finding out how EC using creative work is developed and investigating EC participants’ perception of participating in EC using creative work. This is the exploration of the case study because EC has been practiced for the last four semesters in English Education. The data to be analyzed were collected from the observation and questionnaire from 40 participants of EC and the data analysis used Triangulation. The findings showed that all facilitators and participants get involved to opt, adjust and match the materials over steps and strategy. They opt for one of the programs following their interest and talent. Based on the questionnaire computation using SPSS, from the highest scale 5, the average of participants’ responses is 4,43 for improving their English vocabulary, 4,4 for improving their English speaking skills, 4,35 for improving their English grammar, 4,38 for affecting other academic courses, and 4,38 of dismissing their fear of making mistakes in using English vocabulary. In conclusion, EC using creative work is beneficial to use and it can be a booster and supplement to support participants’ English performance.